MiR-194 as predictive biomarker of responsiveness to neoadjuvant chemoradiotherapy in patients with locally advanced rectal adenocarcinoma. Issue 4 (4th September 2017) - D'Angelo, Edoardo; Zanon, Carlo; Sensi, Francesca; Digito, Maura; Rugge, Massimo; Fassan, Matteo; Scarpa, Marco; Pucciarelli, Salvatore; Nitti, Donato; Agostini, Marco
Abstract : Aims: Curative surgery remains the primary form of treatment for locally advanced rectal cancer (LARC). Recent data support the use of preoperative chemoradiotherapy (pCRT) to improve the prognosis of LARC with a significant reduction of local relapse and an increase of overall survival. Unfortunately, only 20% of the patients with LARC present complete pathological response after pCRT, whereas in 20%–40%,  the response is poor or absent. Methods: We investigated the expression level of miR-194 in n=38 patients with LARC using our public microRNA (miRNA) expression dataset. miR-194 expression was further validated by real-time quantitative PCR (qRT-PCR) and in situ hybridisation (ISH). Protein–protein interaction network and pathway enrichment analysis were performed on miR-194 targets. Results and discussion: Using biopsy samples collected at diagnosis, mir-194 was significantly upregulated in patients responding to treatment (p value=0.016). The data was confirmed with qRT-PCR (p value=0.0587) and ISH (p value=0.026). Protein–protein interaction network and pathway enrichment analysis reveal a possible mechanism of susceptibility to pCRT involving Wnt pathway via its downstream mediator TRAF6. Finally, we interrogated the Comparative Toxicogenomics Database database in order to identify those chemical compounds able to mimic the biological effects of miR-194 as new possible therapeutic option in LARC treatment. The present study combining miRNA expression profiling with integrative computational biology identified miR-194 as predictive biomarker of response to pCRT. Using known and predicted drug mechanism of action, we then identified possible chemical compounds for further in vitro validation.